Systemic Overview of Microstrip Patch Antenna's for Different Biomedical Applications - Govind Arora; Paramjot Maman; Ameya Sharma; Nitin Verma; Vivek Puri (Tabriz University of Medical Sciences, 2021)
Timely diagnosis is the most important parameter for the detection and hindrance with tissues (infected). Many conventional techniques are used for the determination of the chronic disease like MRI, X-ray, mammography, ultrasound and other diagnosing methods. Nevertheless, they have some limitations. We epitomize between 4 and 34 % of all carcinogenic tissues are lacking because of weak, in adequate malignant/benign cancer tissue on the contrary. So, an effective alternative method is the valid concern in the field of medical right now. Imaging with the help of patch antenna to detect chronic disease like breast cancer, oxidative stress syndrome etc. it has been proved to be a suitable potential method, and there are many works in this area. All materials have different conductivity and permittivity. With the help of these antennas, a 3D tissue structure which has different conductivity and permittivity is modelled in high-frequency structure simulator through finite element method which resolves electromagnetic field values and a microstrip patch antenna operation process. As compared with conventional antennas, micro strip patch antennas have enhanced benefits and better prospects. An integrated Antenna plays an important or crucial role for supporting many applications in biomedical, commercial and in military fields. The Antenna designed for these applications should be wideband, not sensitive to the human body. In this present review, the precise application of the Antenna in different biomedical aspects is considered. Furthermore, the author has also discussed the analytical results using simulation models and experimental results for some of the significantdisease.